Silk Sericin Nanomaterials: A Sustainable Frontier in Advanced Biomedical and Cosmetic Applications - , Anna Kaushik; , Manihar Talukdar; , Bidisha Saikia; , Swagata Dehingia; , Arsha A. Sangma (Archives of Current Research International, 2025)
Silk sericin, a hydrophilic protein extracted from silkworm cocoons, is increasingly recognized as a sustainable and multifunctional biomaterial with wide-ranging applications in the biomedical and cosmetic sectors. Its inherent properties—including excellent biocompatibility, biodegradability, antioxidant potential, and moisture retention—have positioned it as a promising candidate for eco-conscious innovations. The integration of sericin with nanotechnology has further amplified its utility by enhancing bioavailability, active ingredient stability, and controlled release capabilities. In biomedical applications, sericin-based nanomaterials have demonstrated notable efficacy in wound healing, tissue engineering, and targeted drug delivery systems, where they contribute to accelerated cellular proliferation, collagen synthesis, and precise therapeutic action. Concurrently, in the cosmetic industry, sericin nanoparticles offer substantial benefits such as improved skin hydration, elasticity, anti-aging, and whitening effects, aligning with consumer demand for natural and environmentally friendly skincare formulations. This review highlights the most recent advancements in sericin extraction methods, functional modifications, and nano-formulations, with a focus on their mechanisms of action, clinical relevance, and industrial applicability. It also critically assesses the challenges related to large-scale production, regulatory compliance, and formulation stability. By consolidating insights from both biomedical and cosmetic fields, this work underscores sericin’s pivotal role as a sustainable nanomaterial capable of advancing circular bioeconomy goals and driving next-generation innovations in health and wellness industries.